Evaluation of anthelmintic and antioxidant efficacy of green-synthesized copper nanoparticles derived from Erioglossum rubiginosum leaf and seed aqueous extracts - Md. Al-Imran Imon; Sharmin Nur Toma; S.M. Sohag; Md. Jakaria Islam; Md. Monirul Islam; Md. Shihab Uddin Sohag; Imran Mahmud; Naznin Shahria; Sanjay Dutta (Elsevier, 2024)
The green synthesis of copper nanoparticles refers to the preparation of nanoparticles using eco-friendly and sustainable processes, often involving plant extracts, microorganisms, or other natural sources. As a sustainable approach with many potential applications, plant extracts could be used for the green synthesis of copper nanoparticles. The green synthesis of copper nanoparticles from plants, such as Erioglossum rubiginosum, involves using leaf and seed extracts to reduce copper ions to form nanoparticles. Primarily, copper nanoparticles are confirmed by visual observation of the aluminum vessel's inner wall exhibiting a glossy, reddish-brown precipitate. Further, the UV-Vis spectrophotometer is employed to detect the presence of CuNPs. The peak is at 631 nm, which is unique to CuNPs. FTIR data show the presence of a capping agent which stabilizes copper nanoparticles. The peaks at 3,265 cm−1 for the hydroxy group (H-bonded OH stretch) indicate alcohols and phenols; 1610 cm−1 for aromatic ring stretch; and 1,075 cm−1 for aliphatic fluoro compounds (C-F stretch). DPPH reducing power assay is used to verify the antioxidant activity. Both plant extracts and the synthesized CuNPs showed considerable antioxidant activity. The seed and leaf extract of Erioglossum rubiginosum used for the green synthesis of copper nanoparticles served as a capping agent due to the presence of antioxidant phytoconstituents. Then, we used Paramphistomum cervi to evaluate the anthelmintic activity of aqueous extracts of leaves and seeds of Erioglossum rubiginosum. After that, we assessed the anthelmintic activity of the green synthesized copper nanoparticles (CuNPs). We observed that the extracts showed a significant and dose-dependent decrease in the paralysis time and death time of parasites whereas better activity was found from the synthesized CuNPs. At last, we claim that comprehensive investigation on plant extracts and CuNPs could be carried out for further study and might pave the way for development of novel therapeutic agents that show efficacy against diverse parasitic infections.